2022
DOI: 10.1038/s41699-021-00280-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth of high-quality semiconducting tellurium films for high-performance p-channel field-effect transistors with wafer-scale uniformity

Abstract: Achieving high-performance p-type semiconductors has been considered one of the most challenging tasks for three-dimensional vertically integrated nanoelectronics. Although many candidates have been presented to date, the facile and scalable realization of high-mobility p-channel field-effect transistors (FETs) is still elusive. Here, we report a high-performance p-channel tellurium (Te) FET fabricated through physical vapor deposition at room temperature. A growth route involving Te deposition by sputtering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…The optimal annealing temperature ( T A ) was less than 250 °C, as shown in Figure S8. When T A is ≥300 °C, the photo-electric property of the phototransistor disappeared completely due to the conversion of the hexagonal Te phase to the orthorhombic TeO 2 phase ( E G = 2.7 eV) and/or the resulting degradation of the TeO x /IGTO stack . To evaluate the performance of our TeO x /IGTO p–n junction phototransistors, we compared our obtained experimental results with datasets from previous reports, as summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal annealing temperature ( T A ) was less than 250 °C, as shown in Figure S8. When T A is ≥300 °C, the photo-electric property of the phototransistor disappeared completely due to the conversion of the hexagonal Te phase to the orthorhombic TeO 2 phase ( E G = 2.7 eV) and/or the resulting degradation of the TeO x /IGTO stack . To evaluate the performance of our TeO x /IGTO p–n junction phototransistors, we compared our obtained experimental results with datasets from previous reports, as summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…When T A is ≥300 °C, the photo-electric property of the phototransistor disappeared completely due to the conversion of the hexagonal Te phase to the orthorhombic TeO 2 phase (E G = 2.7 eV) and/or the resulting degradation of the TeO x /IGTO stack. 48 To evaluate the performance of our TeO x /IGTO p−n junction phototransistors, we compared our obtained experimental results with datasets from previous reports, as summarized in Table 1. The performance of the TeO x / IGTO phototransistors is comparable to those of other phototransistors reported in the literature that combine an AOS and various absorption materials.…”
Section: Resultsmentioning
confidence: 99%
“…This distinguishable difference in the crystallinity, especially after the passivation, can be attributed to stabilization of interfacial energy [6]. It also can partially originate from reduction process during the deposition of Al2O3 passivation layer because of (1) the stronger oxidation potential of Al than Te and (2) low Gibbs formation energy of Al2O3 [6]. This alternate explanation is supported by results of X-ray photoelectron spectroscopy (XPS) as shown in Figure 3(b), where it was confirmed that the formation of Te 4+ phase located around 576 eV in the XPS spectra is considerably suppressed.…”
Section: Experimental Methodsmentioning
confidence: 98%
“…CMOS TFTs using n-channel IGZO and p-channel Te were patterned by metal shadow masks. This distinguishable difference in the crystallinity, especially after the passivation, can be attributed to stabilization of interfacial energy [6]. It also can partially originate from reduction process during the deposition of Al2O3 passivation layer because of (1) the stronger oxidation potential of Al than Te and (2) low Gibbs formation energy of Al2O3 [6].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation